LEGAL PROTECTION FOR CAR RENTAL COMPANIES IN THE EVENT OF BREACH OF THE RENTAL AGREEMENT(CASE STUDY AT PT. BALI GEDE RENT CAR) - Dr.Anak Agung Sagung Ngurah Indradewi,S.H.,M.H; Ngurah Putu Susma Ari Surya Diputra,S.H.,M.H (International Conference on Multidisciplinary Research Perspective, 2025)
Implementing the lease agreement, if a debtor (tenant) does not do what has been agreed upon, he will be said to be in default. So he is negligent or negligent or denial. Problems in implementing the lease agreement will arise in the practice of renting a car, it turns out that the debtor or tenant only paid part of the rent which was not in accordance with the agreed agreement, in this case the debtor is in default. In this study, the author conducted research on car rental service providers at PT. Bali Gede Rent Car which provides daily, weekly, and monthly car rentals for private individuals. renting vehicles in the minibus category throughout Bali, providing vehicle storage for rent during the contract period, opening car rentals and car rental franchises, facilitate consumers by providing drivers, both within the city and outside the city at certain rates according to the company's terms and conditions. The driver's price does not include accommodation, therefore it is important for legal protection for the party renting out the car when carrying out car rental activities. Data obtained at PT. Bali Gede Rent Car in the last three (3) years, namely 2023, 2024 and 2025. In 2023 there were 8 cases, in 2024 there were 2 cases, in 2025 there were 5 cases. Based on this, this study raises two problem formulations, namely: 1. Why is the car rental agreement used as the basis for renting cars at PT. Bali Gede Rent Car? and 2. What form of legal protection is provided to the car rental company if the car renter experiences default on the car rental agreement at PT Bali Gede Rent Car? This type of research is descriptive empirical research using primary and secondary data sources where the data collection techniques field research techniques and interviews where the data obtained will be processed and analyzed using the Qualitative Descriptive method. The conclusion of this study is that the car rental agreement is used as the basis for car rental because the rental agreement is an absolute requirement that must be completed before giving the car keys to be rented ,where in the rental agreement there are rules that explain the mechanism of car rental and sanctions that will be imposed if the rental agreement is violated where point - point in the rental agreement must be obeyed by both parties. Forms of legal protection for car rental companies if the car renter defaults on the car rental agreement is a guarantee and compensation provisions contained in the car rental agreement where the car rental agreement starts with the process of picking up the car which is preceded by checking and returning which also ends with checking the condition of the car being rented out, so as to prevent default from both the lessee car or rental car party